Important Factors Influencing Audit Quality And Audit Opinion - Dekeng Setyo Budiarto; Dicky Prasetya Nugraha (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Agency theory explains that there is a conflict of interest between shareholders and company managers because of the different amounts of information. External auditors who were independent third parties can mediate to reduce this problem. This research examines the influence of solvency, audit lag, and good corporate governance on audit quality and opinion. The object of this research is 47 banks listed on the Indonesia Stock Exchange. The data used are financial reports published from 2018-2022. The analysis results show that only 35 banks meet the criteria as samples. The research results show that audit lag does not affect audit opinion, while the hypothesis significantly impacts both audit lag and audit opinion. This research provides recommendations to shareholders and company owners to improve governance to obtain an audit opinion that meets expectations.